PEMAKNAAN GAMBAR KARTUN â€œCLEKITâ€ PADA HARIAN KORAN JAWA POS (STUDI SEMIOTIKA GAMBAR KARTUN CLEKIT PADA HARIAN JAWA POS EDISI 19 NOVEMBER 2016) - Setiawan, R. Dimas Firman; Yuliyanti, Tri; Nasution, Ute Chairus (representamen, 2017)
This study is based on the meaning of clekit cartoon images. Cartoon drawing as a means ofsocial criticism often we meet in this media, in the era of the media today is usually a case that is pouredinto the cartoon to make the news more interesting. The formulation of the problem of this research is themeaning and message whether contained in cartoon picture clekit daily Newspaper Jawa Pos editionNovember 19, 2016.Teori Sanders Peirce argue that the sign is formed through a relationship of triangle,ie the sign associated with the object to be analyzed with icons, indexes, and symbols in Charles SandersPierce semiotics. The method used is semiotic analysis which is included in descriptive qualitativeresearch. Here the qualitative method uses Sanders Sanders Pierce theory, by using the sign of the icons,indexes, and symbols. The results of this study based on the analysis of data that can be from the meaningof clekit cartoon images, which produces the meaning and message contained in cartoon images clekitdaily newspaper Java Post of 19 November 2016 edition.Keywords : Semiotics, cartoon image, meaning of cartoon clekit